2018
DOI: 10.1007/s10103-018-2529-2
|View full text |Cite
|
Sign up to set email alerts
|

A split-face study: comparison of picosecond alexandrite laser and Q-switched Nd:YAG laser in the treatment of melasma in Asians

Abstract: To evaluate efficacy and safety of picosecond 755 nm alexandrite laser as compared to 1064 nm QS-Nd:YAG laser for melasma treatment in Asians. Twelve patients received 4 sessions of treatments at 1-month interval in a split-face manner. The right side of each patient's face received 755 nm picosecond laser, and the other side received 1064 nm QS-Nd:YAG laser. Zoom handpiece of 755 nm picosecond laser at fluence of 0.88-1.18 J/cm was applied. The treatment protocol used for 1064 nm QS-Nd:YAG laser was 8 mm spot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
37
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 24 publications
5
37
0
2
Order By: Relevance
“…In a recent prior study, PS lasers were shown to be superior to QS lasers in direct comparison for the treatment of melasma on the face . In our centers, melasma treatment with the PS laser showed moderate improvement (Figure = B&A pic) and minimal side effects, consistent with prior studies having similar success while others had mixed success . With that being said, the main issue of melasma is its high recurrence rate, which is independent of the technology used.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In a recent prior study, PS lasers were shown to be superior to QS lasers in direct comparison for the treatment of melasma on the face . In our centers, melasma treatment with the PS laser showed moderate improvement (Figure = B&A pic) and minimal side effects, consistent with prior studies having similar success while others had mixed success . With that being said, the main issue of melasma is its high recurrence rate, which is independent of the technology used.…”
Section: Discussionsupporting
confidence: 87%
“…The nature of the disease—partial remission and high recurrence rate—still rendered laser toning imperfect for the treatment of melasma in one study . In a recent prior study, PS lasers were shown to be superior to QS lasers in direct comparison for the treatment of melasma on the face . In our centers, melasma treatment with the PS laser showed moderate improvement (Figure = B&A pic) and minimal side effects, consistent with prior studies having similar success while others had mixed success .…”
Section: Discussionsupporting
confidence: 82%
“…3 Treatment with a picoseconds laser was successful in one setting with no recurrence after 12 months.The picoseconds lasers generate ultrashort pulses in a trillionth of a second leading to a predominance of a photoacoustic effect rather than a photothermal one. While the efficacy of picoseconds lasers in tattoos is beyond doubt, superiority in the treatment of benign pigmented conditions compared to Q-switched nanosecond lasers was reported in split-face studies 4,5. Reports of conditions unresponsive to the Q-switched nanosecond lasers, which subsequently cleared with the picoseconds laser-as is the case in our patient-further proves the superior efficacy of the picoseconds lasers 6.…”
supporting
confidence: 72%
“…Although previous reports with a variety of fractionated and non-fractionated modalities have shown limited success, the risks of rapid recurrence, rebound hyperpigmentation, and developing mottled hypopigmentation are significant. To date, picosecond laser has been used to treat melasma in one case series; one prospective open-label trial; four prospective, randomized, split-face trials; and one randomized controlled trial involving a cumulative total of 140 patients [56][57][58][59][60][61][62]. Choi et al [57] conducted a randomized single-blind split-face clinical trial involving 39 patients with melasma.…”
Section: Melasmamentioning
confidence: 99%